Combined Effect of Dimethyl Dicarbonate (DMDC) and Nisin on Indigenous Microorganisms of Litchi Juice and its Microbial shelf life. Issue 8 (19th August 2013) - Yu, Yuanshan; Wu, Jijun; Xiao, Gengsheng; Xu, Yujuan; Tang, Daobang; Chen, Yulong; Zhang, Yousheng
Abstract The individual and combined influences of dimethyl dicarbonate (DMDC) and nisin (200 IU/mL) at mild heat on the inactivation of indigenous microorganisms in litchi juice, including bacteria, molds and yeasts (M&Y), were investigated. The fresh litchi juice with or without nisin were exposed to 250 mg/L DMDC at 30, 40, or 45 °C for 0.5, 1, 2, 3, 4, or 6 h. A complete inactivation of M&Y in the litchi juice with or without nisin was achieved as exposed to 250 mg/L DMDC at 30, 40, or 45 °C for 0.5 h. The bacteria, especially Bacillus sp. and Leuconstoc mesenteroides showed higher resistance than M&Y in the litchi juice. Bacillus sp. and Leuconstoc mesenteroides in the litchi juice was not completely inactivated by 250 mg/L DMDC at 30, 40, or 45 °C. However, nisin addition can enhanced the inactivation of these bacteria by DMDC, and nisin and DMDC also showed a synergistic effect on the inactivation of bacteria. M&Y and bacteria were not detected in the litchi juice added with 200 IU/mL nisin as exposed to 250 mg/L DMDC at 45 °C for 3 h. In addition, microbial shelf life of the litchi juice during storage at 4 °C also was evaluated as treated by 250 mg/L DMDC or combination with nisin at 45 °C for 3 h.